Daughter of daring : the trick-riding, train-leaping, road-racing life of Helen Gibson, Hollywood's first stuntwoman - O'Meara, Mallory (Hanover Square Press, 2025)
A biography of stunt performer Helen Gibson, known as "the most daring actress in pictures" during the Golden Age of Hollywood.